Belgium : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper illustrates the recent evolution in Belgian housing prices. Belgian housing prices peaked at the end of 2013 after a persistent increase that was almost continuous for 30 years. The stabilization of prices, combined with policy changes on the fiscal and macro-prudential fronts, raises the question how housing prices are likely to evolve and how a price decline would affect the Belgian economy. The paper assesses the risk of a rapid price correction and the potential repercussions for the real economy. It also argues that an orderly and limited decline in housing prices-coupled with a marginal negative effect on the real economy-is the most plausible scenario.